Does the Women who are in Entrepreneurship Face Any Challenges or Enjoy Any Facilities To Contribute In The Economy Of Bangladesh? (Global Journal of Management and Business Research, 2023)
Women entrepreneurship can play a vital role in the economic development of Bangladesh because more than half of the total population is women. In this male dominated country, the numbers of women entrepreneurs are rapidly increasing. Almost in every sector, women are in a noticeable percentage. The journey of women sometimes easy or sometimes difficult. The main objective of this research is to find out the problems regarding women entrepreneurship and find out the benefits that they enjoy to contribute in Bangladesh economy. This research is being conducted based on the Khulna region. A well-structured questionnaire was developed for the findings part to collect the valid data from the female entrepreneurs. Sample size of this survey was twenty five which are randomly selected. In this research we have found that there are so many scopes that our women entrepreneurs enjoy; they have the freedom to do the business, dealing with men in field does not drain them, Money lender does not put excessive pressure for returning money, intermediaries does not interrupt them to get the right price of the products etc.
Keywords: women; entrepreneurship; challenges; facilities; economy